Obstructive sleep apnea manifested as an atypical major depressive disorder: a case report and review of the literature - Rui,Lopes (2013)
Background: Sleep disorders can be related to loss, disruption or inappropriate day-night rhythm of sleep and represent a great economic burden, involving morbidity and mortality. The insomnia or hypersomnia, secondary to a psychiatric disorder such as depression or psychosis, is frequent in psychiatric practice. Moreover, although uncommon, primary sleep disorders can also cause psychological or psychiatric problems, with some interdependence, which is not completely understood. Case presentation: A 48-year-old woman presented atypical depressive symptoms resistant to antidepressants. In this atypical state, she also showed excessive daytime sleepiness (EDS), snoring, daytime naps and cognitive symptoms. After a sleep study with polysomnography, an obstructive sleep apnea (OSA) manifested as atypical depression was diagnosed. Remission of depressive symptoms was verified with additional continuous positive airway pressure (CPAP) therapy. Conclusion: The awareness that OSA could be presented as an atypical depression allows its early detection and treatment, and possibly the prevention of numerous medical disorders. Psychiatrists and General Practitioners should be familiar with sleep disorders and psychiatric co-morbidities.